Saccorhiza polyschides—A Source of Natural Active Ingredients for Greener Skincare Formulations - Patrícia Susano; Joana Silva; Celso Alves; Alice Martins; Susete Pinteus; Helena Gaspar; Márcia Inês Goettert; Rui Pedrosa (Molecules, 2022)
The growing knowledge about the harmful effects caused by some synthetic ingredients present in skincare products has led to an extensive search for natural bioactives. Thus, this study aimed to investigate the dermatological potential of five fractions (F1–F5), obtained by a sequential extraction procedure, from the brown seaweed Saccorhiza polyschides. The antioxidant (DPPH, FRAP, ORAC and TPC), anti-enzymatic (collagenase, elastase, hyaluronidase and tyrosinase), antimicrobial (Staphylococcus epidermidis, Cutibacterium acnes and Malassezia furfur), anti-inflammatory (nitric oxide, tumor necrosis factor-α, interleukin-6 and interleukin-10) and photoprotective (reactive oxygen species) properties of all fractions were evaluated. The ethyl acetate fraction (F3) displayed the highest antioxidant and photoprotective capacity, reducing ROS levels in UVA/B-exposed 3T3 fibroblasts, and the highest anti-enzymatic capacity against tyrosinase (IC50 value: 89.1 µg/mL). The solid water-insoluble fraction (F5) revealed the greatest antimicrobial activity against C. acnes growth (IC50 value: 12.4 µg/mL). Furthermore, all fractions demonstrated anti-inflammatory potential, reducing TNF-α and IL-6 levels in RAW 264.7 macrophages induced with lipopolysaccharides. Chemical analysis of the S. polyschides fractions by NMR revealed the presence of different classes of compounds, including lipids, polyphenols and sugars. The results highlight the potential of S. polyschides to be incorporated into new nature-based skincare products.